Consumo de cannabis y su incidencia en el bajo rendimiento académico de un estudiante - Bajaña Villavicencio, Johana Cristina (2020)
At present, cannabis use is one of the most used drugs in the youth population, causing deterioration in the adolescent's quality of life, as it can alter learning and memory. In the present case study, we inquire about cannabis use in a teenager and its impact on the poor academic performance of the Educational Unit “June 23” who manifested slower reactions and coordination between the eyes and hands, extremely large pupils, unstable gait, poor performance and increased school absenteeism. Interviews were conducted, using instruments such as; Evaluation sheet, clinical history, the data collected in the medical history, family psychopathological history, and emergence of the psychopathological picture were analyzed. For the intervention of the patient, a therapeutic scheme of cognitive behavioral cutting is developed, in order to restructure the patient's impaired cognition, reinsert it into their social life, reduce disproportionate physiological manifestations.